Ultrasound-Guided Stellate Ganglion Block Combined with Pharmacological Treatment for Rosacea: A Report of Two Cases - Gao C; Wang F; Zhou L; Zhan W; Min R (Patient Preference and Adherence)
Changjian Gao, Fang Wang, Lulu Zhou, Weiwei Zhan, Rui Min Department of Anesthesiology, the Third Clinical Medical College of China Three Gorges University, Gezhouba Central Hospital of Sinopharm, Yichang, Hubei, 443002, People’s Republic of ChinaCorrespondence: Rui Min, Email 504461407@qq.com Weiwei Zhan, Email 504461407@qq.comAbstract: Rosacea is a chronic inflammatory disease primarily affecting the central facial region, significantly involving the facial blood vessels and the sebaceous gland units associated with hair follicles. The stellate ganglion block (SGB) technique can restore balance to autonomic nervous function by interrupting the impulse conduction of preganglionic and postganglionic sympathetic nerve fibers, thereby alleviating excessive peripheral blood vessel contraction, enhancing tissue blood supply, balancing hormone secretion, and modulating immune responses. SGB has demonstrated remarkable efficacy in treating various skin conditions affecting the head, face, and neck. In our case study, two patients with a disease duration exceeding six months underwent treatment involving oral medications, topical applications, and local cold spray, which yielded unsatisfactory results. Subsequently, our department employed the SGB method guided by multiple ultrasound assessments, resulting in nearly complete resolution of the intractable rosacea lesions in both patients.Keywords: ganglion block, rosacea, stellate ganglion